2002
DOI: 10.1093/ndt/17.9.1678
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation in type 2 diabetic patients: a comparison with matched non-diabetic subjects

Abstract: Patient and graft survival after kidney transplantation was similar in type 2 diabetic and matched non-diabetic subjects, with more amputations occurring in the diabetic group. Thus, at a single-centre level renal transplantation results almost equivalent to those in non-diabetic patients may be achieved in type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 14 publications
1
26
1
4
Order By: Relevance
“…However, starting with Kronson et al [12] , very encouraging results of kidney transplantation in type 2 diabetic patients were recently reported in several studies [6,8,9,13,14] , which have demonstrated a similar graft and patient survival in diabetic and in nondiabetic kidney transplant recipients, despite a slight increase in acute rejection rates in type 2 diabetic recipients [9] . Further supporting kidney transplantation in type 2 diabetic patients is the evidence of an overall improvement in health-related quality of life and in functional performance after kidney transplantation [15] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, starting with Kronson et al [12] , very encouraging results of kidney transplantation in type 2 diabetic patients were recently reported in several studies [6,8,9,13,14] , which have demonstrated a similar graft and patient survival in diabetic and in nondiabetic kidney transplant recipients, despite a slight increase in acute rejection rates in type 2 diabetic recipients [9] . Further supporting kidney transplantation in type 2 diabetic patients is the evidence of an overall improvement in health-related quality of life and in functional performance after kidney transplantation [15] .…”
Section: Discussionmentioning
confidence: 98%
“…The proportion of type 2 diabetic patients requiring renal replacement therapy has drastically increased over the recent years [1,6,8,9] . In one of the previous studies focusing on the outcome of type 2 diabetic recipients, Hirschl et al [10] reported that, in patients without significant vascular complications, survival after kidney transplantation was better than on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outra explicação para este resultado pode ser a imunossupressão utilizada. Outros trabalhos realizados em pacientes DM tipo 1 (Rayhill et al, 2000;Reddy et al, 2003) e DM tipo 2 (Boucek et al, 2002) mostram que a principal causa de óbito é a doença cardiovascular. A principal causa de perda do enxerto renal foi óbito com enxerto funcionante.…”
Section: Proposta Do Estudounclassified
“…A principal causa de perda do enxerto renal foi óbito com enxerto funcionante. Este resultado é semelhante ao revelado em outras publicações da literatura (Kronson et al, 2000;Rayhill et al, 2000;Fresnedo et al, 2002;Boucek et al, 2002).…”
Section: Proposta Do Estudounclassified